Association of objectively measured sedentary behaviour and physical activity with cardiovascular disease risk. (29th August 2020) - Vasankari, Ville; Husu, Pauliina; Vähä-Ypyä, Henri; Suni, Jaana; Tokola, Kari; Halonen, Jari; Hartikainen, Juha; Sievänen, Harri; Vasankari, Tommi
Abstract: Background: We evaluated the association of accelerometer-based sedentary behaviour and physical activity with the risk of cardiovascular disease. Design: The design of this study used a population-based, cross-sectional sample. Methods: A subsample of participants in the Health 2011 Study in Finland used the tri-axial accelerometer (≥4 days, >10 h/day, n  = 1398). Sedentary behaviour (sitting, lying) and standing still in six-second epochs were recognised from raw acceleration data based on intensity and device orientation. The intensity of physical activity was calculated as one-minute moving averages of mean amplitude deviation of resultant acceleration and converted to metabolic equivalents. Metabolic equivalents were categorised to light physical activity (1.5–2.9 metabolic equivalents) and moderate-to-vigorous physical activity (moderate-to-vigorous physical activity≥3.0 metabolic equivalents). Daily sedentary behaviour, standing still, light physical activity and moderate-to-vigorous physical activity were expressed as mean daily total time, accumulated time and number of different bouts (from 30 s to >30 min), mean daily metabolic equivalent and weekly peak metabolic equivalent levels of different bout lengths and number of breaks in sedentary behaviour. The ten-year cardiovascular disease risk was based on the Framingham risk model. Results: The mean number of daily sedentary behaviour bouts was more strongly associated with cardiovascular disease risk than mean daily total time. In the best model, smaller waist circumference, greater value of mean daily metabolic equivalent levels of one-minute bouts, higher accumulated time of moderate-to-vigorous physical activity lasting ≤30 min, higher number of >5 min standing bouts and a higher number of long (>30 min) bouts of light physical activity were significantly associated with lower cardiovascular disease risk (R 2  = 0.836). Conclusions: The objectively measured number and accumulated time from different bout lengths of physical activity and sedentary behaviour were associated with cardiovascular disease risk, which is considered relevant for estimating cardiovascular diseases and for devising preventive actions.